PRESENTATION OF BOND DISCOUNT. - Paton, William A. (The Accounting Review, 1937)
Abstract Included in the "Tentative Statement of Accounting Principles" offered by the American Accounting Association in the Accounting Review of June, 1936, was the recommendation that unaccumulated bond discount be reported in the corporate balance sheet as a contra to the face or maturity amount of the outstanding obligation rather than as an asset. The purpose of advancing this specific suggestion in a statement of general principles was to call attention to a practice which is neither in accord with the clear reasoning which is supposed to characterize accounting nor supported by the "considerations of expediency" so cherished by those who feel it necessary to offer some excuse for deviations from logical procedure. The members of the Executive Committee of the Association felt, in other words, that here was a particular point at which accepted presentation is definitely out of line with sound principle and where correction would be entirely feasible-aside from the problem of inducing the typical accountant to change his ways. The recommendation, it should be understood, does not involve any new doctrine or approach. It represents merely the application to financial statements of the interpretation of bond discount long a commonplace in financial circles.